Myocarditis following COVID-19 mRNA vaccinations: Twin and sibling case series - P. Shenton; D.R. Cheng; P. Simm; B. Jones; N.W. Crawford (Vaccine: X, 2023)
ImportanceMyocarditis and myopericarditis are well described adverse events of special interest (AESI) following COVID-19 vaccinations. Whilst the aetiology is still being investigated; there is evidence that genetic predisposition may be a risk factor for the development of myocarditis. Furthermore, hormones are thought to contribute to sex-specific differences in myocarditis, skewed toward a larger risk in adolescent males. Objective: This unique sibling case series may help highlight potential mechanisms and prognostic factors in the development of myocarditis following COVID-19 vaccination in adolescent males. In this context, twin and familial studies provide a unique epidemiological perspective to investigate the interplay between genetic predisposition and other factors. Participants: Observational case series of all siblings reported to SAEFVIC11 SAEFVIC: Surveillance of Adverse Events Following Vaccination in the Community. with chest pain following COVID-19 vaccinations in Victoria, Australia. Exposure: mRNA vaccination (Comirnaty BNT162b2 COVID-19 (Pfizer-BioNTech) and Spikevax mRNA-1273 (Moderna). Findings: Our case series comprises 6 young males; two sets of monozygotic twins and one set of fraternal brothers following reports of chest pain associated with COVID-19 mRNA vaccination. Five patients were diagnosed with myocarditis as per Brighton Collaboration Criteria (Level 2). The remaining sibling, who did not have myocarditis, was subsequently diagnosed with pubertal delay. Conclusions: Understanding the genetic and hormonal risk factors and aetiology for myocarditis associated with COVID-19 vaccines is paramount. Further evaluation of specific genetic targets or biomarkers is required to understand the implications of population vaccine policy, particularly for adolescent and young adult males at highest risk for this AESI.